Perillyl alcohol has antibacterial effects and reduces ROS production in macrophages - Figueiredo, Rebeca Dantas Alves; Ortega, Adriana Cabrera [UNESP]; González Maldonado, Laura Andrea [UNESP]; de Castro, Ricardo Dias; Ávila-Campos, Mario Julio; Rossa Junior, Carlos [UNESP]; de Aquino, Sabrina Garcia (FapUNIFESP (SciELO), 2020)
Natural products have emerged as a rich source of bioactive compounds for adjunctive treatments of many infectious and inflammatory conditions, including periodontitis. Among the monoterpenes with significant biological properties, there is the perillyl alcohol (POH), which can be found in several essential oils and has shown immunomodulatory properties in recent studies, which may be interesting in the treatment of non-neoplastic inflammatory disorders. Objective: To determine the antibacterial and immune modulatory activities of the POH. Methodology: The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the POH for two significant Gram-negative periodontal pathogens were determined by macrodilution and subculture, respectively. Cell proliferation and cytotoxicity in RAW 264.7 macrophages were determined by Trypan Blue and mitochondrial enzymatic activity assay. The modulation of reactive oxygen species (ROS) was analyzed by flow cytometry and expression of TNF and arginase-1 by real-time PCR. Results: The POH was effective against P. gingivalis (ATCC 33277) and F. nucleatum (ATCC 25586) with MIC= MBC=1600 μM. No cytotoxicity up to 100 µM was observed on macrophages. The cell proliferation was inhibited from 48 hours at 100 μM (p<0.05) and 250 μM (p<0.01). The POH increased ROS production at both 10 μM and 100 μM (p<0.05) in unstimulated cells. The PMA-induced ROS production was not affected by POH, whereas 100 μM significantly reduced lipopolysaccharide-induced (LPS-induced) ROS. The expression of TNF was not affected by POH in unstimulated cells or in cells polarized to M1 phenotype, whereas both concentrations of POH reduced (p<0.05) the expression of arginase-1 in M2-polarized macrophages. Conclusion: The POH has antibacterial activity against periodontal pathogens and reduced proliferation of murine macrophages without significant cytotoxicity at concentrations up to 100 μM. In addition, the POH reduced the LPS-induced ROS and the expression of arginase-1 in M2-polarized macrophages.
Keywords: Immunomodulation; Macrophages; Natural products; Periodontal diseases